2022
DOI: 10.1038/s41598-022-25313-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and renal injury following 2-methyl-4-chlorophenoxyacetic acid (MCPA) poisoning

Abstract: Abstract2-Methyl-4-chlorophenoxyacetic acid (MCPA) is a widely used chlorophenoxy herbicide. MCPA poisoning causes mitochondrial dysfunction, which can lead to kidney injury and death. The objective of this study is to describe the epidemiology, case fatality and extent of renal injury in a large cohort of MCPA self-poisonings. The study consists of two parts: (1) A report of epidemiological data and clinical outcomes in MCPA poisoned patients in Sri Lanka between 2002 and 2019; (2) Evaluation of acute kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Other authors found higher mortality in older patients with higher oral intakes, and did not find significant differences between the value of GCS score and AKI in healthy and deceased [7].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Other authors found higher mortality in older patients with higher oral intakes, and did not find significant differences between the value of GCS score and AKI in healthy and deceased [7].…”
Section: Discussionmentioning
confidence: 77%
“…However, mortality data differ in different reports and for different formulations. Thus, a prospective case study that studied the outcome of intentional poisonings with MCPA and included 181 patients reported a mortality of 4.4% [6]; another epidemiological study with the same formulation on 1653 patients detected a mortality of 5.5% [7].…”
Section: Discussionmentioning
confidence: 99%